1988
DOI: 10.1177/00220345880670091701
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Rate of Release of Intra-oral Mercury Vapor from Amalgam

Abstract: The experimental and analytical difficulties associated with the measurement of mercury vapor in the oral cavity are considerable. In the present paper, the objective was to measure the amount of intra-oral mercury vapor in subjects with amalgams, by means of two sets of equipment based on different functional principles. In addition, it was found that the type of mercury source prevalent in the oral cavity had to be evaluated. The measuring technique used to obtain correct results is discussed, and an evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 6 publications
(7 reference statements)
2
51
1
Order By: Relevance
“…Prolonged exposure to mercury vapor may induce neurological dysfunction and even low-level exposures are reported to produce weakness, anorexia, weight loss and so forth [56]. Changes in personality, loss of memory, depression and occasionally delirium were reported as some of the symptoms when man is exposed to high-level of mercury vapor [57]. [32] evidenced that miners of Abbadia San Salvatore did not suffer exposure to Hg° since no native mercury was present in the ore deposit.…”
Section: Spatial and Temporal Distribution Of Gemmentioning
confidence: 99%
“…Prolonged exposure to mercury vapor may induce neurological dysfunction and even low-level exposures are reported to produce weakness, anorexia, weight loss and so forth [56]. Changes in personality, loss of memory, depression and occasionally delirium were reported as some of the symptoms when man is exposed to high-level of mercury vapor [57]. [32] evidenced that miners of Abbadia San Salvatore did not suffer exposure to Hg° since no native mercury was present in the ore deposit.…”
Section: Spatial and Temporal Distribution Of Gemmentioning
confidence: 99%
“…In interpreting each subject's intra-oral mercury vapor readings, however, Vimy and Lorscheider treated the measurements as though the subject were exposed to room air at those concentrations. Several authors have pointed out their error (Mackert, 1987;Olsson and Bergman, 1987;Berglund et al, 1988;Clarkson et al, 1988). In the paper by Berglund et al (1988), it was shown experimentally that the mercury vapor release from amalgams was a time-dependent process and that the amount of mercury released during a certain time period was independent of the flow rate of the air through the oral cavity during respiration and collection with measuring instruments.…”
Section: Intra-oral Hg Vapor Measurementsmentioning
confidence: 99%
“…In the discussion of ingestion of particulate amalgam, it should be noted that the gastrointestinal absorption of elemental (metallic) mercury is extremely lowon the order of 0.01% (Williams, 1981;Tsalev and Zaprianov, 1983 Two separate investigations (Berglund et al, 1988;Clarkson et al, 1988) have shown that mercury vapor does not continue to build up in the mouth during respiration through the nose. In the study by Berglund (1990), it was calculated that about 75% of the vaporized mercury is dissolved in the saliva and swallowed (the model predicts that 12.5% is inhaled, 12.5% is exhaled, and 75% is swallowed).…”
Section: Jig)mentioning
confidence: 99%
“…This lack of standardisation is reflected in the large variation in their reported data which in turn may also explain the very different conclusions reached by some authors. 18,19 Several bleaching methods exist, including in office bleaching with or without a light source, 20,21 mouth guard bleaching under supervision of a dentist, and bleaching kits that are sold over the counter (where individuals apply the bleaching agent without the supervision of the dentist). We reported previously on metal ion release from dental amalgam following exposure to CP at a single concentration.…”
Section: Introductionmentioning
confidence: 99%